Evolutionary Consequences of Altered Atmospheric Oxygen in Drosophila melanogaster - Charette, Marc; Darveau, Charles-A.; Perry, Steve F.; Rundle, Howard D. (Université d'Ottawa | University of Ottawa, 2011)
Twelve replicate populations of Drosophila melanogaster, all derived from a common ancestor, were independently evolved for 34+ generations in one of three treatment environments of varying PO2: hypoxia (5.0–10.1 kPa), normoxia (21.3 kPa), and hyperoxia (40.5 kPa). Several traits related to whole animal performance and metabolism were assayed at various stages via “common garden” and reciprocal transplant assays to directly compare evolved and acclimatory differences among treatments. Results clearly demonstrate the evolution of a greater tolerance to acute hypoxia in the hypoxia-evolved populations, consistent with adaptation to this environment. Greater hypoxia tolerance was associated with an increase in citrate synthase activity in fly homogenate when compared to normoxic (control) populations, suggesting an increase in mitochondrial volume density in these populations. In contrast, no direct evidence of increased performance of the hyperoxia-evolved populations was detected, although a significant decrease in the tolerance of these populations to acute hypoxia suggests a cost to adaptation to hyperoxia. Hyperoxia-evolved populations had lower productivity overall (i.e., across treatment environments) and there was no evidence that hypoxia or hyperoxia-evolved populations had greatest productivity or longevity in their respective treatment environments, suggesting that these assays failed to capture the components of fitness relevant to adaptation.